Towards a rapid molecular diagnostic for melioidosis: comparison of DNA extraction methods from clinical specimens - Richardson, Leisha J (2011)
Optimising DNA extraction from clinical samples for Burkholderia pseudomallei Type III secretion system real-time PCR in suspected melioidosis patients confirmed that urine and sputum are useful diagnostic samples. Direct testing on blood remains problematic; testing DNA extracted from plasma was superior to DNA from whole blood or buffy coat.